Efficacy, Distancing, and Reconciling: Religion and Race in Americans’ Abortion Attitudes - Bruce, Tricia Colleen (Religions, 2020)
Religion and race together inform Americans’ abortion attitudes, but precisely how remains contradictory and unclear. Presumptions of shared religious or secular “worldviews” dividing abortion opinion mask variation among racially diverse adherents within the same tradition. Theoretical gaps compel a deeper, qualitative exploration of underlying processes. This article uses close analysis of a religiously and racially diverse, ideal-typical subset of in-depth interviews from the National Abortion Attitudes Study to identify three processes operating at the intersection of religion and race in abortion attitudes: efficacy, distancing, and reconciling. While religion’s effect on abortion opinion remains paramount, accounting for social location illuminates meaningful variation. Findings offer an important corrective to overly-simplified narratives summarizing how religion matters to abortion opinion, accounting more fully for complex religion and religion as raced.